Do the selfish mimic cooperators? Experimental evidence from finitely-repeated labor markets - Brian E. Roe; Steven Y. Wu (Institute for the Study of Labor (IZA), 2009)
Experimental studies have consistently shown that cooperative outcomes can emerge even in finitely repeated games. Such outcomes are justified by existing reputation building models, which suggest that cooperative outcomes can be sustained if some subjects have other-regarding preferences. While the existence of other-regarding preferences is typically used to justify experimental outcomes, we are unaware of empirical studies that explicitly examine the interaction between cooperators (those with other-regarding preferences) and selfish subjects in sustaining cooperation. In this paper, we classify subjects as either selfish or cooperative using simple social preference games and then test for behavioral differences between the two types in a finitely-repeated labor market with unenforceable worker effort. Theory predicts, and our data confirms, that (1) selfish players mimic the actions of cooperators when trading partners can track the individual reputation of past partners and (2) selfish and cooperative types act differently when individual reputations cannot be tracked.
urn:nbn:de:101:1-20090330172
Keywords: C91; D31; D86; K12; 330; Contracts; relational contracts; implicit contracts; market interaction; experimental economics; repeated transaction; social preferences; reputation; firm latitude; finitely-repeated games; Arbeitsvertrag; Arbeitsbeziehungen; Soziale Beziehungen; Wiederholte Spiele; Kooperatives Spiel; Implizite Kontrakte; Test